2004
DOI: 10.1111/j.1600-0528.2004.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete dentures and oral health‐related quality of life – do coping styles matter?

Abstract: Wearing conventional complete dentures has a significant impact on OHRQOL. This impact is moderated by the styles a patient uses to cope with stress. Using emotional support has a positive effect on OHRQOL, while other coping styles, namely instrumental support, behavioral disengagement, substance abuse, denial, and religion are significant negative predictors of OHRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 54 publications
5
68
0
5
Order By: Relevance
“…Indeed, previous research has revealed that an individual's coping strategies and self-esteem may be important determinants of OHRQoL. 38,39 Therefore, this study formed part of a larger research project which also investigated the relationship between these variables and children's OHRQoL during educational transition, which will be reported in future communications.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Indeed, previous research has revealed that an individual's coping strategies and self-esteem may be important determinants of OHRQoL. 38,39 Therefore, this study formed part of a larger research project which also investigated the relationship between these variables and children's OHRQoL during educational transition, which will be reported in future communications.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Results can serve as an outcome measure; they allow insight into how a patient’s oral health affects his/her well-being and quality of life at a given point in time [11]. Multiple-item questionnaires are the most widely used method to assess OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Ten of the studies [15,19,20,[45][46][47][48][49][50][51] that conducted item-level analyses reported that the two items from the turning to religion sub-scale formed their own separate factor ( Table 1). Three of these studies [20,49,50] used a sample of university students, but overall, the range was very broad, and included diverse participants groups, such as emergency workers [45], edentulous patients with complete dentures [48], or genetic counselors [51].…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
“…Three of these studies [20,49,50] used a sample of university students, but overall, the range was very broad, and included diverse participants groups, such as emergency workers [45], edentulous patients with complete dentures [48], or genetic counselors [51]. PCA was the stated method of choice for four of the ten studies [15,19,46,50].…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation